2008
DOI: 10.2310/jim.0b013e3181889e13
|View full text |Cite
|
Sign up to set email alerts
|

Inducible Nitric Oxide Synthase Inhibitor SD-3651 Reduces Proteinuria in MRL/lpr Mice Deficient in the NOS2 Gene

Abstract: Several studies have demonstrated the effectiveness of arginine analog nitric oxide synthase (NOS) inhibitor therapy in preventing and treating murine lupus nephritis. However, MRL/MpJ-FASlpr (MRL/lpr) mice lacking a functional NOS2 (inducible NOS [iNOS]) gene (NOS2−/−) develop proliferative glomerulonephritis in a fashion similar to their wild-type (wt) littermates. This finding suggests that the effect of arginine analog NOS inhibitors is through a non-iNOS–mediated mechanism. This study was designed to addr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2009
2009
2025
2025

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…On the other hand, mice given the inhibitor did not develop proteinuria throughout the study [9], suggesting a protective role of NOS inhibition in preventing podocyte injury or dysfunction. This protective effect of NOS inhibition was also supported by a study utilizing N 6 -(1-iminoethyl)- l -lysine, dihydrochloride (L-NIL; a partial, selective inhibitor of iNOS), although the dose used was not selective for inhibition of iNOS [7]. In this study, proteinuria was absent in LNIL-treated MRL/lpr mice lacking the NOS2 gene.…”
Section: Introductionsupporting
confidence: 54%
See 1 more Smart Citation
“…On the other hand, mice given the inhibitor did not develop proteinuria throughout the study [9], suggesting a protective role of NOS inhibition in preventing podocyte injury or dysfunction. This protective effect of NOS inhibition was also supported by a study utilizing N 6 -(1-iminoethyl)- l -lysine, dihydrochloride (L-NIL; a partial, selective inhibitor of iNOS), although the dose used was not selective for inhibition of iNOS [7]. In this study, proteinuria was absent in LNIL-treated MRL/lpr mice lacking the NOS2 gene.…”
Section: Introductionsupporting
confidence: 54%
“…Several studies showed a strong link between inducible nitric oxide synthase (iNOS) expression and development and severity of the disease phenotype in several murine models of lupus nephritis [6,7]. Both MRL/MpJ-Fas lpr /J (MRL/lpr) and (New Zealand Black × New Zealand White) F1 mice develop spontaneous proliferative lupus nephritis.…”
Section: Introductionmentioning
confidence: 99%
“…NOS2−/− mice had elevated anti-dsDNA antibody levels and had, as observed in the past, no significant reductions in glomerular pathology or proteinuria. However, iNOS inhibitor therapy significantly reduced proteinuria and podocyte flattening/eNOS cell swelling by electron microscopy [51]. This suggests that iNOS inhibitor therapy reduces pathologic changes in podocyte and endothelial cell pathology in this model in an iNOS-independent (and possibly eNOS-dependent) fashion.…”
Section: Effects Of Manipulation Of Inos In Murine Lupusmentioning
confidence: 99%
“…However, the importance of increased inducible nitric oxide synthase (iNOS)-mediated nitric oxide (NO) production in LN was questioned when genetic deletion of functional iNOS in lupus mouse models failed to reduce the onset of classic pathologic features of LN except vasculitis (6, 7). However, ROS production in this murine model of lupus nephritis was significantly reduced by inhibitors of iNOS (8), suggesting that driving pathogenic consequence of iNOS expression in LN is the production of SO rather than the production of NO.…”
Section: Introductionmentioning
confidence: 99%